Las fuentes y sus implicaciones en el estudio léxico: Isidoro de Sevilla, Etym. 17.9.2 y Liber Glossarum s. v. ‘Malabatron’ - Ferraces, Antonio (Exemplaria Classica, 2009)
In this article a Latin translation of the De materia medica by Dioscorides is identified as a common source for Isid. Etym. 17,9,2 and Lib. Gloss. s.v. Malabatron (Heiberg, Glossae medicinales, p. 45); secondly, the use of the term folium as a plant name in the Isidore’s Etymologies is explained as a result of a transmission accident in the source’s text.